Ciprofloxacin removal by ultrasound-enhanced carbon nanotubes/permanganate process: In situ generation of free reactive manganese species via electron transfer. (1st September 2021) - Wang, Xuxu; Wang, Ying; Zhao, Chun; Zhu, Yunhua; Sun, Zhihua; Fan, Hua-Jun Shawn; Hu, Xuebin; Zheng, Huaili
Highlights: A novel synergistic technology coupling ultrasound and CNTs/PM (UCP) was developed. Electron-rich organics could be rapidly removed in the UCP process from raw water. RMnS oxidation and electron transfer were the main processes for CIP removal. Ultrasound and CNTs played a critical role in promoting the generation of free RMnS. CNTs could maintain satisfactory efficiency after repeated use in the UCP process. Abstract: Recently, free reactive manganese species (RMnS) generated via permanganate catalytic oxidation technology has been applied to contaminants abatement and sludge dewatering. This study proposed a novel free RMnS generation method in ultrasound enhanced carbon nanotube (CNTs)/permanganate process (UCP) for organics removal. Taking ciprofloxacin as a target contaminant, the removal efficiency in the UCP process (9.78 s − 1 ) was remarkably higher than that of the permanganate (0.71 s − 1 ) and CNTs/permanganate (2.57 s − 1 ) processes. CNTs could enrich manganese compounds and ciprofloxacin, and act as an electronic platform for the electronic transfer from ciprofloxacin to manganese compounds for free RMnS generation, which was revealed by DFT calculation and spectrum analysis. Meanwhile, ultrasound further regulated the generation of RMnS as it could transform the inactive solid Mn(IV) into free RMnS. In the UCP process, non-free radical modes including RMnS oxidation (49.8%) and electron transfer (23.5%) were the dominant processes for ciprofloxacin removal in the UCP process, and hydroxyl radical oxidation (13.2%), CNTs adsorption (5.5%), and PM oxidation (8.0%) also contributed to ciprofloxacin removal. Interestingly, CNTs could be well reused in the UCP process as more than 88.75% of ciprofloxacin was removed after five times reuse of CNTs. The UCP process provides a novel strategy for rapid contaminants removal in water treatment via continuous generation of free RMnS. Graphical abstract: Image, graphical abstract